Prehrambene navike i stanje ishrane školske dece u gradskim i seoskim sredinama - Živanović, Srđan (PONS - medicinski časopis, 2021)
Introduction: Proper nutrition means satisfying organism’s needs for daily intake of energy and adequate amount of nutritional and protective substances which are essential for maintenance of physiological functions of organism and health. The aim of this study was to determine eating habits and nutritional status of school children.Methods: The research was designed as a cross-section study. It was carried out in primary school “Sveti Sava’’ in Foča and primary school “Sveti Sava’’ in Gacko, branch in Avtovac. The study included 110 pupils aged from 10 to 14 years. As a measuring instrument, anthropometric measurements (height and weight) were used as well as a questionnaire.Results: The questionnaire included primary school pupils of different gender and age. Among the respondents, there were 66 (60%) boys and 44 (40%) girls. Most of the pupils (80,9%) had normal body weight, 48 (43,6%) boys and 41 (37,3%) girls. Among overweight pupils, there was statistically significant larger number of male pupils who were  overweight in comparison with female pupils (χ2=8,490; p=0,037). Also, there was statistically significant larger number of overweight pupils from urban environment in comparison with pupils from the rural one (χ2=8,614; p=0,035). Most of the pupils regularly have breakfast (50,9%). There is statistical significance in that larger number of children from urban environment consume fast food daily in comparison with children from rural environments (χ2=10,187; p=0,006).Conclusion: Eating habits of the elementary school children are not satisfying, being reflected in frequent skipping of breakfast, overconsumption of sandwiches, snacks and candies, while healthy foods, such as fish and vegetables are deficient in nutrition.
Keywords: nutrition; percentile; obesity; physical activity